The role of the interfacial interactions in the quasibinary theory of eutectics - Zakarian, D.A. (Reports of the National Academy of Sciences of Ukraine, 2016)
Within the framework of the unified theory based on the method of pseudopotentials, the thermodynamic potential of an eutectic composite is constructed. The effect of interfacial interactions on the concentrations and the temperature of the material at the eutectic point is considered. A new interpretation of the mechanism of formation of the eutectic is suggested.